Lipocalin-2 is a sensitive and specific marker of bacterial iInfection in children - Herberg,J; Huang,H; Thezenas,M; Janes,V; Carter,M; Gormley,S; Hamilton,M; Kessler,B; Levin,M; Casals-Pascual,C (bioRxiv, 2019)
Abstract Introduction Bacterial infection is the leading cause of death in children globally. Clinical algorithms to identify children who are likely to benefit from antimicrobial treatment remain suboptimal. Biomarkers that accurately identify serious bacterial infection (SBI) could improve diagnosis and clinical management. Lipocalin 2 (LCN2) and neutrophil collagenase (MMP-8) are neutrophil-derived biomarkers associated with bacterial infection. Methods We evaluated LCN2 and MMP-8 as candidate biomarkers in 40 healthy controls and 151 febrile children categorised confirmed SBI, probable SBI, or viral infection. The diagnostic performance of LCN2 and MMP-8 to predict SBI was estimated by the area under the receiver operating characteristic curve (AUROC) and compared to the performance of C-reactive protein (CRP). Results Plasma LCN2 and MMP-8 concentration were predictive of SBI. The AUROC (95% CI) for LCN2, MMP8 and CRP to predict SBI was 0.88 (0.82-0.94); 0.80 (0.72-0.87) and 0.89 (0.84-0.94), respectively. The diagnostic performance of LCN2 in combination with CRP was significantly superior to either marker alone: AUROC 0.92 (95% CI: 0.88-0.96). Conclusion LCN2 is a sensitive and specific predictor of SBI in children which could be used to improve clinical management and antimicrobial stewardship. LCN2 should be further evaluated in prospective clinical studies.